Formal grammar : 20th and 21st International Conferences, FG 2015, Barcelona, Spain, August 2015, revised selected papers, FG 2016, Bozen, Italy, August 2016, proceedings /: 20th and 21st International Conferences, FG 2015, Barcelona, Spain, August 2015, revised selected papers, FG 2016, Bozen, Italy, August 2016, proceedings. (2016) - Unknown
No abstract available